The Sandman. The complete first season [videorecording (DVD)] - Gaiman, Neil; Goyer, David S.; Heinberg, Allan (Warner Bros. Entertainment Inc., 2023)
There is another world that waits for all of us when we close our eyes and sleep, a place called the Dreaming, where the Sandman, Master of Dreams, gives shape to all of our deepest fears and fantasies. But when Dream is unexpectedly captured and held prisoner for a century, his absence sets off a series of events that will change both the dreaming and waking worlds forever.